2000
DOI: 10.1023/a:1007878523663
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Myocardial contractile function after coronary artery bypass graft surgery is often depressed and may require inotropic support, particularly in patients on treatment with beta-adrenergic and Ca2+ blockers. In view of the increase in cytosolic Ca2+ during early reperfusion, use of Ca2+ sensitizing agents may be preferable to adrenergic agonists for enhancement of contractile function after cardioplegic arrest. The aim of this study was to assess the efficacy of the Ca2+ sensitizer, levosimendan, as an inotrope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…It exerts its positive inotropic effect by sensitizing cardiac troponin C to calcium during systole, thus increasing cardiac performance without increasing myocardial oxygen consumption. Levosimendan also has a weak arrhythmogenic effect [22]. Our group demonstrated for the first time the efficacy of levosimendan in improving myocardial dysfunction after deep hypothermia-rewarming [11].…”
Section: Discussionmentioning
confidence: 99%
“…It exerts its positive inotropic effect by sensitizing cardiac troponin C to calcium during systole, thus increasing cardiac performance without increasing myocardial oxygen consumption. Levosimendan also has a weak arrhythmogenic effect [22]. Our group demonstrated for the first time the efficacy of levosimendan in improving myocardial dysfunction after deep hypothermia-rewarming [11].…”
Section: Discussionmentioning
confidence: 99%
“…Xanthos et al 44 reported that the combination of epinephrine, atenolol, and levosimendan, when given during cardiac arrest and resuscitation in a pig model, resulted in improved 48-hour survival and postresuscitation cardiac function. Concurrently, Lochner et al 45 reported that the effects of levosimendan were not blunted by the presence of beta-blockers, as in the case of adrenergic inotropes.…”
Section: Origins Of a Unique Cardiovascular Agentmentioning
confidence: 97%
“…[ 44 ] Concurrently, Lochner et al reported that the effects of levosimendan were not blunted by the presence of beta-blockers, as in the case of adrenergic inotropes. [ 45 ]…”
Section: Origins Of a Unique Cardiovascular Agentmentioning
confidence: 99%